2021
DOI: 10.5334/dsj-2021-018
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Vocabulary and Metadata Schema for Materials Science Data Discovery

Abstract: The International Materials Resource Registries (IMRR) working group of the Research Data Alliance (RDA) was created to spur initial development of a federated registry system to allow for easier discovery and access to materials data. As part of this effort, a controlled vocabulary and metadata schema were developed with contributions from members of the working group and other experts. Here we describe the process, the resulting vocabulary and XML schema, and lessons learned in the development and use of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Metadata refer to information that describes other data [28,29] and are essential for finding and understanding data [30,31]. Traditional metadata typically consist of keywords, but different organizations have different standards for assigning keywords.…”
Section: Materials Data Discovery Protocolmentioning
confidence: 99%
“…Metadata refer to information that describes other data [28,29] and are essential for finding and understanding data [30,31]. Traditional metadata typically consist of keywords, but different organizations have different standards for assigning keywords.…”
Section: Materials Data Discovery Protocolmentioning
confidence: 99%
“…The MDF (Material Science Data Facility), sponsored by the National Institute of Standards (NIST) and the Center for Hierarchical Materials Design (CHIMaD), now hosts about 578 datasets (116 experimental datasets) and indexes over 970,000 records of Materials data from other repositories as of December 2021. Other recent efforts include infrastructure for a federated registry of information resources for materials science (Plante et al 2021) ; a proposed controlled vocabulary and metadata schema for materials discover (Medina-Smith et al 2021); and a new experimental infrastructure under development for the integration of Electronic Lab Notebooks and data archiving systems with materials science workflows (Brandt et al 2021). In industry, software platforms (e.g.…”
Section: Studies Of Practices In Experimental Msementioning
confidence: 99%
“…The survey also found that researchers rarely used metadata schema but did follow a standard file-naming scheme (Joo and Peters, 2020). While a regulated file-naming system is necessary, applying a good metadata schema makes the data more useful by allowing more in-depth searches and text mining (Medina-Smith et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%